Ferritic stainless steel sheet and manufacturing method
The ferritic stainless steel sheet with enhanced magnetic properties and corrosion resistance is achieved through controlled composition and manufacturing processes, addressing the needs of smaller and lighter electronic devices.
Patent Information
- Application Number
- JP2022568244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-08
- Filing Date
- 2021-12-03
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-12-03
AI Technical Summary
Existing ferritic stainless steels used in electronic devices require further improvement in soft magnetic properties and corrosion resistance to meet the demands of smaller and lighter electronic devices.
A ferritic stainless steel sheet with a magnetized area ratio of 50% or more, specific chemical composition, and controlled crystal orientation, along with a manufacturing process involving cold rolling, annealing, and adjustment annealing to enhance soft magnetic properties and corrosion resistance.
The solution results in a ferritic stainless steel plate with improved soft magnetic properties and corrosion resistance, suitable for electronic devices.
Smart Images

Figure 0007618699000004 
Figure 0007618699000001 
Figure 0007618699000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel sheet and a manufacturing method thereof. [Background technology]
[0002] Soft magnetic materials, which have large magnetization and permeability and can change magnetization depending on the direction and magnitude of an external magnetic field, are used in solenoid valves, magnetic heads, various sensors, etc. in electronic devices. For example, Ni-Fe alloys called permalloys and Ni-plated electromagnetic steel sheets have been widely used as soft magnetic materials.
[0003] On the other hand, the soft magnetic materials mentioned above contain a lot of Ni, and therefore the material cost is high. Therefore, the use of ferritic stainless steel, which is relatively inexpensive and has good corrosion resistance, as the soft magnetic material has been considered. For example, Patent Documents 1 and 2 disclose soft magnetic ferritic stainless steel sheets with improved magnetic properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-120420 [Patent Document 2] Japanese Patent Application Publication No. 5-255817 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for smaller and lighter electronic devices, and the soft magnetic ferritic stainless steels used in electronic devices are also required to have improved magnetic properties, i.e., improved soft magnetic properties, in order to satisfy the above demands.
[0006] However, the ferritic stainless steels disclosed in Patent Documents 1 and 2 leave room for further study in terms of soft magnetic properties and corrosion resistance.
[0007] In view of the above, an object of the present invention is to solve the above problems and provide a ferritic stainless steel sheet having good magnetic properties, more specifically, good soft magnetic properties and good corrosion resistance. [Means for solving the problem]
[0008] The present invention has been made to solve the above-mentioned problems, and is summarized as the following ferritic stainless steel sheet and manufacturing method.
[0009] (1) A ferritic stainless steel sheet having a magnetized area ratio of 50% or more.
[0010] (2) Chemical composition, in mass percent: C: 0.015% or less, Si: 3.0% or less, Mn: 1.0% or less, S: 0.0040% or less, P: 0.08% or less, Al: 0.80% or less, N: 0.030% or less, Cr: 15.0~25.0%, Mo: 0.5-3.0%, Ti: 0 to 0.50%, Nb: 0-0.50%, Ni: 0 to 0.50%, Cu: 0% or more and less than 0.1% Zr: 0-1.0%, V: 0-1.0%, REM: 0~0.05%, B: 0~0.01%, The balance is Fe and impurities. The ferritic stainless steel sheet according to the above (1), which satisfies the following formula (i): 0.10≦Ti+Nb≦0.50 (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.
[0011] (3) The chemical composition is, in mass%, Si: 0.60% or less, The ferritic stainless steel sheet according to (2) above, which contains
[0012] (4) The chemical composition is, in mass%, Ni: 0.05 to 0.50%, Cu: 0.01% or more and less than 0.1% Zr: 0.01-1.0%, V: 0.01 to 1.0%, REM: 0.005-0.05%, and B: 0.0002~0.01%, The ferritic stainless steel sheet according to the above (2) or (3), comprising one or more selected from the following:
[0013] (5) The pitting corrosion resistance index PREN calculated by the following formula (ii) is 20.0 or more, In the RD direction crystal orientation, Represented by the following formula (iii): <001> The total area of grains parallel to the direction S <001> and, <111> The total area of grains parallel to the direction S <111> The ferritic stainless steel sheet according to any one of the above (1) to (4), in which F1, which is the ratio of F to F, is 5.0 or more. PREN = Cr + 3.3Mo + 16N (ii) F1=S <001> / S <111> (iii) In the above formula (ii), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
[0014] (6) A ferritic stainless steel sheet according to any one of (1) to (5) above, in which the maximum grain size observed is 500 μm or more.
[0015] (7) A method for producing a ferritic stainless steel sheet according to any one of (1) to (4) above, comprising the steps of: a cold rolling step of performing cold rolling at a cold rolling reduction rate of 75% or more using rolls having a diameter of 100 mm or less; A manufacturing method comprising: a cold-rolled sheet annealing step of performing annealing after the cold rolling step.
[0016] (8) A method for producing the ferritic stainless steel sheet according to (5) or (6) above, comprising the steps of: a cold rolling process in which cold rolling is performed at a cold rolling reduction rate of 80% or more using rolls having a diameter of 90 mm or less; A manufacturing method comprising: a cold-rolled sheet annealing step of performing annealing after the cold rolling step.
[0017] (9) A method for producing the ferritic stainless steel sheet according to (5) or (6) above, comprising the steps of: Further, after the cold-rolled sheet annealing step, annealing for adjusting the crystal orientation is performed one or more times, In the adjustment annealing step, The manufacturing method according to (8) above, wherein the annealing atmosphere is an inert gas atmosphere or a vacuum atmosphere, the annealing temperature is in the range of more than 750° C. and not more than 1350° C., the annealing time is in the range of 4 hours or more, and the heating rate until the annealing temperature is reached is less than 30° C. / min. Effect of the Invention
[0018] According to the present invention, it is possible to obtain a ferritic stainless steel sheet having good magnetic properties, more specifically, good soft magnetic properties and good corrosion resistance. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a magnetic domain observation microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present inventors have conducted studies on improving the soft magnetic properties of ferritic stainless steel sheets and have obtained the following findings (a) to (c).
[0021] (a) Increasing the Si content can increase the magnetic flux density and improve the soft magnetic properties. On the other hand, increasing the Si content can decrease workability and manufacturability. For this reason, it is desirable to reduce the Si content while still containing Cr and Ti, which are effective in improving the soft magnetic properties. In addition, the inclusion of Mo can improve the corrosion resistance.
[0022] (b) In addition, in order to improve the soft magnetic properties of the steel sheet, it is desirable to control the magnetized area ratio observed with a magnetic domain observation microscope so that it is 50% or more. In order to achieve a magnetized area ratio of 50% or more, it is preferable to perform cold rolling with a roll diameter of 100 mm or less and adjust the cold rolling reduction rate at that time to 75% or more. As a result, in the RD (rolling direction) plane orientation, the texture of the steel sheet is difficult to develop in the normal process and is effective in improving the soft magnetic properties. <001> A well-oriented structure can be obtained.
[0023] (c) In addition, <001> In order to obtain a texture with a more developed orientation, in addition to the usual annealing of the cold-rolled sheet, it is preferable to perform annealing for adjusting the orientation (also simply referred to as "adjustment annealing") at least once. In the adjustment annealing, it is preferable to set the annealing temperature to a range of more than 750°C and less than 1350°C, and the annealing time to 4 hours or more. Furthermore, it is preferable to reduce the heating rate up to the above annealing temperature to less than 30°C / min. This makes it possible to obtain a stronger <001> The orientation on the γ-fiber, which reduces the magnetization area ratio, is also reduced. As a result, the soft magnetic properties are improved.
[0024] An embodiment of the present invention has been made based on the above findings. Each requirement of this embodiment will be described in detail below.
[0025] 1. Magnetization area ratio As mentioned above, soft magnetic properties are characterized by the fact that a material is easily magnetized when a magnetic field is applied and easily returns to its original state when the magnetic field is removed. Magnetic flux density is used as a criterion for evaluating magnetic properties. Magnetic flux density is an index of the strength of a magnetic field, but evaluation of soft magnetic properties requires not only the strength of the magnetic field but also the ease of magnetization and the ease of return.
[0026] Therefore, in the ferritic stainless steel sheet of this embodiment, the magnetized area ratio described below is set to 50% or more. Furthermore, by setting the magnetized area ratio to 50% or more, not only the magnetic flux density but also the ease of magnetization and the ease of return become good, and the soft magnetic properties are improved. In addition, the magnetized area ratio has a good correlation with the magnetic flux density, and the magnetic flux density can also be increased. In order to obtain better soft magnetic properties, the magnetized area ratio is preferably set to 70% or more, more preferably 80% or more, and even more preferably 90% or more. The upper limit of the magnetized area ratio is not particularly set. It is 100% or less.
[0027] Here, the magnetized area ratio will be described. The magnetized area ratio is the ratio of the magnetized area to the area of the observation field of view expressed as a percentage, and is calculated using the magnetic property analysis method described in JP 2021-162425 A. In this magnetic property analysis method, for example, as shown in FIG. 1, a magnetic domain observation microscope equipped with a light source, an electromagnet, a lens, a detector, and a magnetic property analysis device is used. The magnetic domain observation microscope utilizes the effect that the polarization state changes when incident light having linear polarization is reflected on the magnetized sample surface, that is, the Kerr effect. The magnetic domain observation microscope detects the reflected light from the surface obtained by the Kerr effect. Specifically, a difference in contrast occurs before and after the application of a magnetic field. The magnetized area ratio is measured from this difference in contrast.
[0028] The magnetic domain observation microscope used for the magnetization area ratio in this application is Neomagnesia Lite manufactured by NeoArc Corporation, and uses a white LED as the light source and a Wyeth-type electromagnet as the electromagnet. First, the amount of change in reflected light intensity is measured when no magnetic field is applied to the sample, and a threshold value for the amount of change in reflected light intensity is set so that 99% of the observation area is determined to be unmagnetized. Next, when a magnetic field of 1000 Oe is applied to the sample, areas that exceed the set threshold value are extracted as magnetized areas, and the area ratio is calculated as the magnetization area ratio. Observation is performed in three fields of view within a magnification range of 1000 to 2500 times.
[0029] 2.Chemical composition The chemical composition of the ferritic stainless steel sheet of this embodiment is preferably within the following ranges. The reasons for limiting each element are as follows. In the following description, "%" for the content means "mass %".
[0030] C: 0.015% or less C combines with other elements to form carbides, which reduces the soft magnetic properties. For this reason, the C content is preferably 0.015% or less. The C content is more preferably 0.010% or less. The C content is further preferably 0.008% or less. It is preferable to reduce the C content as much as possible, but excessive reduction increases the manufacturing cost. For this reason, the C content is preferably 0.001% or more.
[0031] Si:3.0% or less Although Si has a deoxidizing effect and is an element that improves soft magnetic properties, if it is contained in excess, the soft magnetic properties are deteriorated. In addition, the workability is also deteriorated. For this reason, the Si content is preferably 3.0% or less. The Si content is preferably 1.5% or less. In the steel sheet of this embodiment, it is preferable to reduce the Si content in order to increase the magnetization area ratio described later to 70% or more. Specifically, the Si content is more preferably 0.60% or less. On the other hand, in order to obtain the deoxidizing effect, the Si content is preferably 0.01% or more.
[0032] Mn: 1.0% or less Mn has a deoxidizing effect and an effect of improving strength. However, if Mn is contained in excess, the soft magnetic properties are degraded. In addition, there are cases where the workability is degraded. For this reason, the Mn content is preferably 1.0% or less. The Mn content is more preferably 0.50% or less, and further preferably 0.30% or less. On the other hand, if the Mn content is excessively reduced, the manufacturing cost increases. For this reason, the Mn content is preferably 0.10% or more.
[0033] S: 0.0040% or less S is an impurity contained in steel that reduces soft magnetic properties. For this reason, the S content is preferably 0.0040% or less. The S content is more preferably 0.0020% or less. It is preferable to reduce the S content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the S content is preferably 0.0001% or more.
[0034] P:0.08% or less P is an impurity contained in steel that reduces soft magnetic properties. For this reason, the P content is preferably 0.08% or less. The P content is more preferably 0.05% or less. It is preferable to reduce the P content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the P content is preferably 0.005% or more.
[0035] Al: 0.80% or less Al is an element that has a deoxidizing effect, and by reducing impurities through deoxidization, it has the effect of improving soft magnetic properties. However, if Al is contained in excess, the soft magnetic properties are degraded. For this reason, the Al content is preferably 0.80% or less. The Al content is more preferably 0.30% or less, and even more preferably 0.25% or less. On the other hand, in order to obtain the above effect, the Al content is preferably 0.01% or more.
[0036] N: 0.030% or less N may be contained in steel as an impurity, and may combine with other elements to form nitrides, which may reduce soft magnetic properties and cold workability. For this reason, the N content is preferably 0.030% or less. The N content is more preferably 0.020% or less. It is preferable to reduce the N content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the N content is preferably 0.005% or more.
[0037] Cr: 15.0~25.0% Cr has the effect of improving corrosion resistance. In addition, since Cr is a ferrite generating element, it also has the effect of improving soft magnetic properties. In particular, when Si is reduced, the soft magnetic properties may deteriorate. In such a case, it is desirable to increase the Cr content. Therefore, the Cr content is preferably 15.0% or more, and more preferably 16.0% or more. However, if Cr is excessively contained, the soft magnetic properties deteriorate. Therefore, the Cr content is preferably 25.0% or less, more preferably 20.0% or less, and even more preferably 18.5% or less.
[0038] Mo: 0.5-3.0% Mo has the effect of improving corrosion resistance. It is also a ferrite stabilizing element and has the effect of improving soft magnetic properties. In particular, when Si is reduced, the soft magnetic properties may be deteriorated, so it is desirable to increase the Mo content, as with Cr. For this reason, the Mo content is preferably 0.5% or more, and more preferably 1.0% or more. However, excessive Mo content increases the cost and deteriorates the soft magnetic properties. For this reason, the Mo content is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.6% or less.
[0039] In addition to the above elements, one or more elements selected from Ti, Nb, Ni, Cu, Zr, V, REM, and B may be contained within the ranges shown below. The reasons for limiting the amount of each element will be explained.
[0040] Ti: 0 to 0.50% Ti has the effect of improving corrosion resistance and workability. Furthermore, it has the effect of suppressing the formation of martensite phase that reduces soft magnetic properties, and contributes to improving soft magnetic properties. Therefore, it is preferable to contain Ti alone or together with Nb, which has a similar effect, as necessary. However, excessive inclusion of Ti reduces workability. For this reason, the Ti content is preferably 0.50% or less. The Ti content preferably satisfies the formula (i) described below.
[0041] Nb: 0 to 0.50% Like Ti, Nb has the effect of improving corrosion resistance and workability. Furthermore, it has the effect of suppressing the formation of martensite phase that reduces soft magnetic properties, thereby improving soft magnetic properties. Therefore, it is preferable to contain Nb alone or together with Ti, which has a similar effect, as necessary. However, excessive content reduces workability. For this reason, the Nb content is preferably 0.50% or less. The Nb content preferably satisfies the formula (i) described below.
[0042] Here, it is preferable that the Ti content and the Nb content satisfy the following formula (i). 0.10≦Ti+Nb≦0.50 (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.
[0043] If the side value in formula (i), which is the total content of Ti and Nb, is less than 0.10%, it becomes difficult to obtain the above-mentioned effects of improving corrosion resistance, workability, and soft magnetic properties. Therefore, the side value in formula (i) is preferably 0.10% or more. The side value in formula (i) is more preferably 0.20% or more. However, if the side value in formula (i) exceeds 0.50%, the workability tends to decrease. Therefore, the side value in formula (i) is preferably 0.50% or less. The side value in formula (i) is more preferably 0.40% or less.
[0044] Ni: 0 to 0.50% Ni has the effect of improving corrosion resistance and toughness. Therefore, it may be contained as necessary. However, if Ni is contained in excess, the soft magnetic properties are reduced. Therefore, the Ni content is preferably 0.50% or less, and more preferably 0.40% or less. On the other hand, in order to obtain the above effect, the Ni content is preferably 0.05% or more.
[0045] Cu: 0% or more and less than 0.1% Cu has the effect of improving corrosion resistance. Therefore, it may be contained as necessary. However, excessive Cu content reduces workability. Also, the manufacturing cost increases. Therefore, the Cu content is preferably less than 0.1%, and more preferably 0.05% or less. On the other hand, in order to obtain the above effect, the Cu content is preferably 0.01% or more.
[0046] Zr: 0-1.0% Zr has the effect of improving toughness and cold forgeability. Therefore, it may be contained as necessary. However, if Zr is contained in excess, the soft magnetic properties are reduced. Therefore, the Zr content is preferably 1.0% or less, and more preferably 0.5% or less. On the other hand, in order to obtain the above effect, the Zr content is preferably 0.01% or more.
[0047] V: 0 to 1.0% V has the effect of improving toughness and cold forgeability. Therefore, it may be contained as necessary. However, if an excessive amount of V is contained, the soft magnetic properties are deteriorated. Therefore, the V content is preferably 1.0% or less, and more preferably 0.5% or less. On the other hand, in order to obtain the above effect, the V content is preferably 0.01% or more.
[0048] REM: 0~0.05% REM acts as a deoxidizing element and has the effect of reducing impurities. Therefore, it may be contained as necessary. However, if an excessive amount of REM is contained, the soft magnetic properties are deteriorated. Therefore, the REM content is preferably 0.05% or less, and more preferably 0.03% or less. On the other hand, in order to obtain the above effect, the REM content is preferably 0.005% or more.
[0049] B: 0 to 0.01% B has the effect of improving soft magnetic properties and processability. Therefore, it may be contained as necessary. However, if an excessive amount of B is contained, the soft magnetic properties are deteriorated. Therefore, the B content is preferably 0.01% or less, and more preferably 0.005% or less. On the other hand, in order to obtain the above effect, the B content is preferably 0.0002% or more.
[0050] Pitting corrosion resistance index In the chemical composition of the ferritic stainless steel sheet of this embodiment, the pitting corrosion resistance index PREN calculated by the following formula (ii) is preferably 20.0 or more in order to obtain the desired corrosion resistance. In order to obtain better corrosion resistance, the pitting corrosion resistance index PREN is more preferably 22.0 or more.
[0051] PREN = Cr + 3.3Mo + 16N (ii) In the above formula (ii), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
[0052] In the chemical composition of the steel sheet of the present embodiment, the balance is preferably Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present embodiment.
[0053] 3.Crystal orientation In the ferritic stainless steel sheet according to the present embodiment, the ferritic oxide film is usually difficult to develop, but is effective in improving the soft magnetic properties. <001> Therefore, in the RD direction crystal orientation, the following formula (iii) is used: <001> The total area of grains parallel to the direction S <001> and, <111> The total area of grains parallel to the direction S <111> It is preferable that F1, which is the ratio of F1 to RD, is 5.0 or more. Note that RD is an abbreviation for Rolling Direction, and refers to the rolling direction. F1=S <001> / S <111> (iii)
[0054] If the above-mentioned F1 is less than 5.0, the RD crystal orientation is not effective in improving the soft magnetic properties. <001> The orientation is not sufficiently developed. Therefore, F1 is preferably 5.0 or more, and more preferably 10.0 or more. There is no particular upper limit for F1, but it is usually 10,000.0 or less.
[0055] Where: <001> The grains parallel to the direction are those whose crystal orientation is <001> It refers to grains that are within 15 degrees of the direction. <111> The grains parallel to the direction are those whose crystal orientation is <111> This refers to grains that deviate from the normal direction by less than 15°.
[0056] Above S <001> and S <111> The measurement can be performed using EBSD. The magnification is 100x, and two fields of view are selected. Each field of view is irradiated with an electron beam at a step size (measurement pitch) of 0.5 μm to create a crystal orientation map. At this time, image analysis software is used to measure the S <001> and S <111> It is sufficient to calculate
[0057] 4. Maximum grain size By controlling the grain size by performing the adjustment annealing described later, the soft magnetic properties of the steel sheet can be further improved. Specifically, it is preferable to control the grain size so that it becomes coarse, and it is preferable that the maximum grain size of the observed grains is 500 μm or more, and more preferably, the maximum grain size is 1000 μm or more. It is preferable that the average grain size of the observed grains is 100 μm or more.
[0058] By controlling the crystal grains to have a size within the above range, the crystal orientation can be controlled and the value of F1 can be set within a preferred range. The maximum crystal grain size is calculated by observing using EBSD and examining the largest value among the grain sizes of each crystal grain calculated by approximating the circle equivalent using image analysis software. Similarly, the average grain size is calculated by calculating the average value of the grain sizes of each crystal grain. The measurement conditions for EBSD are the same as those described above.
[0059] 5. Plate thickness In the ferritic stainless steel sheet of this embodiment, from the viewpoint of processing, the sheet thickness is preferably 3 mm or less, and more preferably 2 mm or less.
[0060] 6. Manufacturing method A preferred method for producing the ferritic stainless steel sheet of this embodiment will be described below.
[0061] 6-1. Melting to hot rolling process A steel having the above-mentioned chemical composition is melted and cast by a conventional method to obtain a steel slab to be subjected to hot rolling. Then, hot rolling is performed by a conventional method. The conditions during hot rolling are not particularly limited, but usually, the heating temperature of the steel slab is set to 1000 to 1300°C, and the rolling reduction is preferably in the range of 90.0 to 99.9%. In this way, a hot-rolled sheet is obtained. After hot rolling, pickling and hot-rolled sheet annealing are performed as necessary. The annealing temperature of the hot-rolled sheet is not particularly limited, but usually, it is performed in the range of 750 to 1100°C. It is more preferable to set it in the range of 850 to 950°C.
[0062] 6-2.Cold rolling process Next, the hot-rolled sheet that has undergone the above steps is cold-rolled to obtain a cold-rolled sheet. In the cold rolling, it is preferable to use rolls with a diameter of 100 mm or less. If a roll with a diameter of more than 100 mm is used, it is difficult to introduce shear strain. As a result, in the RD crystal orientation, <111> While the orientation grows preferentially, <001> The growth of the orientation is suppressed. As a result, the value of F1 decreases, and the magnetization area ratio also decreases. Therefore, it is preferable to use a roll with a diameter of 100 mm or less. Here, in order to make the value of F1 5.0 or more and to further increase the magnetization area ratio, it is more preferable to use a roll diameter of 90 mm or less, and even more preferable to use a roll diameter of 80 mm or less.
[0063] In addition, the reduction ratio during cold rolling (also referred to as "cold rolling reduction ratio") is preferably 75% or more. If the cold rolling reduction ratio is less than 75%, a sufficient reduction ratio cannot be obtained, and the desired plate thickness cannot be obtained. <001> The orientation does not grow sufficiently, and the value of F1 decreases, resulting in a decrease in the magnetized area ratio. For this reason, the cold rolling reduction is preferably 75% or more. In order to make the value of F1 5.0 or more and to further increase the magnetized area ratio, the cold rolling reduction is more preferably 80% or more. The cold rolling reduction is further preferably 85% or more. The upper limit of the cold rolling reduction is not particularly set, but is usually 99% or less.
[0064] 6-3.Cold-rolled sheet annealing process Subsequently, after the cold rolling process, the cold rolled sheet is annealed (hereinafter, also referred to as "cold rolled sheet annealing"). In the cold rolled sheet annealing, the annealing temperature and the annealing time are not particularly limited, but usually, the annealing temperature is in the range of 800 to 1100°C, and the annealing time (holding time) is in the range of 0 to 120 minutes. Note that other conditions may also be adjusted appropriately and as necessary. After the cold rolled sheet annealing, the sheet is cooled once to 300°C. In addition, after the cold rolled sheet annealing, pickling may be performed as necessary.
[0065] 6-4. Annealing process for adjustment After the cold-rolled sheet annealing process, it is preferable to perform adjustment annealing, which is annealing for adjusting the crystal orientation of the cold-rolled sheet, at least once. By performing this adjustment annealing under appropriate conditions, the value of F1 can be further increased and the maximum grain size can be made 500 μm or more, which results in an improvement in the value of the magnetized area ratio.
[0066] The adjustment annealing includes additional annealing performed without processing after cold-rolled sheet annealing, and magnetic annealing performed after processing after cold-rolled sheet annealing. In the adjustment annealing, only additional annealing may be performed. In addition, adjustment annealing may be performed twice, such as when additional annealing is performed, processing is performed, and magnetic annealing is performed. After cold-rolled sheet annealing, processing is performed without additional annealing, and only magnetic annealing may be performed. Note that by performing adjustment annealing, grains that are coarser than those in the cold-rolled annealed sheet are usually formed.
[0067] 6-4-1. Annealing atmosphere In the preparation annealing, the annealing atmosphere is preferably an inert gas atmosphere or a vacuum atmosphere in order to suppress oxidation of the steel sheet surface and suppress the formation of oxides and nitrides on the steel sheet surface.
[0068] 6-4-2. Annealing temperature and heating rate In the preparation annealing, it is preferable that the annealing temperature is in the range of more than 750°C and not more than 1350°C, and the annealing time is in the range of 1 to 24 hours. <001> The orientation does not grow sufficiently, and the value of F1 becomes small. In addition, the crystal grains do not grow easily, and the maximum grain size becomes less than 500 μm. For this reason, the annealing temperature is preferably more than 750 ° C, and more preferably 900 ° C or more. For the same reason, the annealing time is preferably 1 h or more. In addition, if it is desired to make the magnetization area ratio 70% or more, the annealing time in the adjustment annealing is preferably 4 h or more.
[0069] On the other hand, if the annealing temperature exceeds 1350°C, recrystallization proceeds too much, resulting in a random structure, making it difficult to obtain the desired texture. In addition, there is a concern that the soft magnetic properties may be deteriorated due to the generation of martensite phase during the cooling process. For this reason, the annealing temperature is preferably 1350°C or less, and more preferably 1000°C or less. In addition, since a long annealing time leads to a decrease in production efficiency, the annealing time is preferably 24 hours or less.
[0070] Here, the heating rate until the annealing temperature is reached is preferably less than 30°C / min. In the production of normal steel sheets, the heating rate is generally increased from the viewpoint of suppressing the coarsening of crystal grains, but in the steel sheet of the present embodiment, it is preferable to slow down the heating rate and raise the temperature slowly. This is because if the heating rate is 30°C / min or more, the temperature rise will proceed too abruptly, and <001> This is because the crystal grains in the azimuth direction do not grow. As a result, the value of F1 becomes small, and it becomes difficult to sufficiently improve the soft magnetic properties, and in particular, it becomes difficult to make the magnetization area ratio 70% or more. For this reason, the heating rate is preferably less than 30°C / min, and more preferably 10°C / min or less.
[0071] Thereafter, cooling is performed to obtain a steel sheet. At this time, the cooling and other conditions may be adjusted so that the structure of the steel sheet becomes that of a ferritic stainless steel sheet.
[0072] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples. EXAMPLES
[0073] Steel slabs having the chemical compositions shown in Table 1 were manufactured, and the resulting steel slabs were heated in the temperature range of 1200° C. and hot-rolled at a rolling reduction of 90% or more to obtain hot-rolled sheets.
[0074] [Table 1]
[0075] After hot rolling, the steel sheet was annealed at 975°C, followed by pickling and the like. Next, the roll diameter and rolling reduction were adjusted under the conditions shown in Table 2, and cold rolling was performed. Then, cold-rolled sheet annealing and pickling were performed at 920°C for 1 minute, and the steel sheet was cooled to obtain a ferritic stainless steel sheet. In some examples, in addition to the above-mentioned cold-rolled sheet annealing and the like, adjustment annealing (additional annealing) was further performed under the conditions shown in Table 2, and the steel sheet was cooled to obtain a ferritic stainless steel sheet. The annealing atmosphere during adjustment annealing (additional annealing) was a vacuum.
[0076] [Table 2]
[0077] The magnetized area ratio, crystal orientation, and crystal grain size (maximum grain size and average grain size) of the obtained steel sheets were examined. In addition, to evaluate the properties, magnetic flux density was measured and a salt spray test was performed. These measurements and tests were performed according to the following procedures.
[0078] (Magnetized area ratio) The magnetic domain observation microscope used in the measurement of the magnetized area ratio was Neomagnesia Lite manufactured by NeoArc Corporation, and a white LED was used as the light source, and a Wyeth-type electromagnet was used as the electromagnet. Then, first, the amount of change in the reflected light intensity was measured when no magnetic field was applied to the sample, and the case where 99% of the observation area was unmagnetized was examined. Next, when a magnetic field of 1000 Oe was applied to the sample, the area exceeding the set threshold was extracted as a magnetized area, and the magnetized area ratio was calculated. Here, the external magnetic field was applied in the rolling direction. The threshold may be set by selecting any intensity from the contrast intensity of the observed image before and after the application of the magnetic field. In this case, the contrast intensity as the threshold was set so that 99% of the observation area observed before the application of the magnetic field was included as an unmagnetized state. The observation was performed in three fields of view at a magnification range of 1000 to 2500 times.
[0079] (Crystal orientation) The crystal orientation was measured using EBSD. The observation surface was the rolled surface after the thickness was reduced to the center of the plate, the magnification was 100x, and two measurement fields were selected. Each field was irradiated with an electron beam at a step size (measurement pitch) of 0.5 μm to create a crystal orientation map. Image analysis software was used to measure the S <001> and S <111> was calculated.
[0080] (Maximum and average particle size) The maximum grain size was calculated by observing the L-section of the steel sheet using EBSD and examining the largest value among the grain sizes of each crystal grain calculated by approximating the circle equivalent using image analysis software. Similarly, the average grain size was calculated by calculating the average value of the grain size of each crystal grain. The EBSD measurement conditions were the same as those described above. For the example in which additional annealing was not performed, the maximum grain size and average grain size of the steel sheet obtained through the process without additional annealing were measured by EBSD. Similarly, for the example in which additional annealing was performed, the maximum grain size and average grain size of the steel sheet obtained through additional annealing were measured by EBSD.
[0081] (Magnetic flux density measurement) The magnetic flux density was measured by a ring test using a BH tracer, and the magnetic flux density B5 value was measured. A magnetic flux density of 0.40 T or more was evaluated as good, and a magnetic flux density of less than 0.40 was evaluated as poor.
[0082] (Salt spray test) The salt spray test was conducted based on JIS Z 2371:2015. Specifically, a sample was cut out from the obtained steel plate, salt water was sprayed onto the surface of the sample, and 24 hours later, the sample surface was visually observed to confirm the occurrence of rust. In Table 3, A denotes a sample with no rust, B denotes a sample with a small amount of distributed rust spots but with a rusted area of less than 10%, and C denotes a sample with a rusted area of 10% or more. Furthermore, E denotes a sample with a surface condition even better than A.
[0083] The samples used in each measurement and test were taken from the center in the width direction, which has an average metal structure. The results are summarized in Table 3 below.
[0084] [Table 3]
[0085] Nos. 1 to 23, which satisfy the requirements of this embodiment, had good magnetic flux density and no rusting was observed, so that they had good soft magnetic properties and corrosion resistance. On the other hand, Nos. 24 to 35, which do not satisfy the requirements of this embodiment, had low magnetization area ratio, poor magnetic flux density, rusting was observed, and so on, resulting in poor soft magnetic properties and / or corrosion resistance.
[0086] Among the examples, Nos. 2, 4, 14, and 15 were subjected to additional annealing and satisfied the more preferable manufacturing conditions of this embodiment, and therefore had F1 values of 5.0 or more and magnetized area ratios of 70% or more, exhibiting the best soft magnetic properties.
[0087] On the other hand, in the case of No. 10, the heating rate during additional annealing was slightly high, so the value of F1 was slightly lower, and the soft magnetic properties were inferior to those of the above-mentioned Nos. 2, 4, 14, and 15. In the case of No. 11, the annealing temperature during additional annealing was slightly low, so the maximum grain size was smaller, and the soft magnetic properties were inferior to those of the above-mentioned Nos. 2, 4, 14, and 15. In the case of No. 12, the rolling reduction during cold rolling was slightly low, so the value of F1 was slightly lower, and the soft magnetic properties were inferior to those of the above-mentioned Nos. 2, 4, 14, and 15. Similarly, in the case of No. 13, the roll diameter during cold rolling was slightly large, so the value of F1 was slightly lower, and the soft magnetic properties were inferior to those of the above-mentioned Nos. 2, 4, 14, and 15. In the case of No. 22, the Si content was high, so the magnetic flux density was high, but the magnetization area ratio was lower.
[0088] In addition, for example, between examples where additional annealing was performed under preferred conditions and examples where additional annealing was not performed, such as No. 1 and No. 2, and No. 3 and No. 4, the example where additional annealing was performed under preferred conditions had an increased F1 value and improved soft magnetic properties. Note that, in the case of No. 23, the annealing time during additional annealing was less than 4 hours, so the magnetized area ratio was less than 70%.
[0089] Among the comparative examples, Nos. 24 to 31, whose chemical compositions do not satisfy the preferred requirements of this embodiment, did not satisfy the requirements for the magnetization area ratio, and the soft magnetic properties were degraded. In addition, No. 32 did not satisfy the requirements for the magnetization area ratio, and the soft magnetic properties were degraded, because the roll diameter during cold rolling was large and the rolling reduction was small. In addition, the value of F1 also decreased. In No. 33, the rolling reduction was small during cold rolling, so even after additional annealing, the magnetization area ratio was low and the soft magnetic properties were degraded. In addition, the value of F1 also decreased. In No. 34, the roll diameter during cold rolling was large, so even after additional annealing, the magnetization area ratio was low and the soft magnetic properties were degraded. In addition, the value of F1 also decreased. In No. 35, the roll diameter during cold rolling was large, so the magnetic flux density value was relatively good, but the value of the magnetization area ratio was degraded.
Claims
1. The chemical composition, in mass percent, is C: 0.015% or less, Si: 3.0% or less, Mn: 1.0% or less, S: 0.0040% or less, P: 0.08% or less, Al: 0.80% or less, N: 0.030% or less, Cr: 15.0-25.0%, Mo: 0.5-3.0%, Ti: 0 to 0.50%, Nb: 0 to 0.50%, Ni: 0 to 0.50%, Cu: 0% or more and less than 0.1% Zr: 0 to 1.0%, V: 0 to 1.0%, REM: 0-0.05%, B: 0 to 0.01%, The balance is Fe and impurities (excluding Sn: 0.005% or more). The following formula (i) is satisfied: A ferritic stainless steel sheet having a magnetized area ratio of 50% or more when a magnetic field of 1000 Oe is applied. 0.10≦Ti+Nb≦0.50...(i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.
2. The chemical composition, in mass%, Si: 0.60% or less, The ferritic stainless steel sheet according to claim 1, containing
3. The chemical composition, in mass%, Ni: 0.05-0.50%, Cu: 0.01% or more and less than 0.1% Zr: 0.01 to 1.0%, V: 0.01-1.0%, REM: 0.005 to 0.05%, and B: 0.0002-0.01%, The ferritic stainless steel sheet according to claim 1 or 2, comprising one or more selected from the following:
4. The pitting corrosion resistance index PREN calculated by the following formula (ii) is 20.0 or more, In the RD crystal orientation, The total area S of crystal grains oriented parallel to the <001> direction is represented by the following formula (iii): <001> and the total area S of crystal grains oriented parallel to the <111> direction. <111> The ferritic stainless steel sheet according to any one of claims 1 to 3, wherein F1, which is a ratio of F1 to F2, is 5.0 or more. PREN=Cr+3.3Mo+16N...(ii) F1=S <001> / S <111> ・・・(iii) In the above formula (ii), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
5. The ferritic stainless steel sheet according to any one of claims 1 to 4, wherein the maximum grain size observed is 500 µm or more.
6. A method for producing the ferritic stainless steel sheet according to any one of claims 1 to 3, comprising the steps of: a cold rolling step of performing cold rolling at a cold rolling reduction rate of 75% or more using rolls having a diameter of 100 mm or less; A manufacturing method comprising: a cold-rolled sheet annealing step of performing annealing after the cold rolling step.
7. A method for producing the ferritic stainless steel sheet according to claim 4 or 5, comprising the steps of: a cold rolling step of performing cold rolling at a cold rolling reduction rate of 80% or more using rolls having a diameter of 90 mm or less; A manufacturing method comprising: a cold-rolled sheet annealing step of performing annealing after the cold rolling step.
8. The method further includes an adjustment annealing step in which annealing for adjusting crystal orientation is performed one or more times after the cold-rolled sheet annealing step, In the adjustment annealing step, The annealing atmosphere is an inert gas atmosphere or a vacuum atmosphere, the annealing temperature is in the range of more than 750 ° C. and less than 1350 ° C., the annealing time is in the range of 4 h or more, and the heating rate until the annealing temperature is reached is less than 30 ° C. / min. The manufacturing method according to claim 7.
Citation Information
Patent Citations
Corrosion resistant soft magnetic material
JP1993255817A
Corrosion resistant soft-magnetic steel
JP1996120420A
Production of high cr ferritic hot rolling stainless steel sheet with smooth face
JP1997174114A
Soft magnetic stainless steel sheet and its production
JP2000064000A
Vibration-damping ferritic stainless steel material and manufacturing method
JP2017039955A